DIY couture : create your own fashion collection - Martin, Rosie (London : Laurence King, 2012)
The 'DIY Couture' collection is 10 stylish, easy to make pieces of clothing that can be endlessly reinvented in different fabrics, textures and colours. Anyone who enjoys sewing and creating something unique will love using this book to make their own couture wardrobe.
boek